2004
DOI: 10.1177/154405910408300713
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution of Food Boluses after Mastication of Six Natural Foods

Abstract: There is a large variability between and among individuals in the physiology of mastication, but it is not known whether this produces a similar variability in the particle sizes of food boluses at the end of the chewing process. Food boluses obtained just before swallowing were analyzed in ten subjects (aged 36.7 +/- 9.5 yrs) with normal dentition. Food samples of 3 nuts (peanut, almond, pistachio) and 3 vegetables (cauliflower, radish, and carrot) were chewed and expectorated after self-estimated complete ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
192
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(219 citation statements)
references
References 21 publications
22
192
2
3
Order By: Relevance
“…Peyron et al, 2004). Similarly they suggested that a minimum level of lubrication was necessary to swallow the bolus and again they represented this threshold as a plane across the degree of lubrication axis.…”
Section: Resultsmentioning
confidence: 99%
“…Peyron et al, 2004). Similarly they suggested that a minimum level of lubrication was necessary to swallow the bolus and again they represented this threshold as a plane across the degree of lubrication axis.…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence of differences in particle sizes after a standardized number of chews, between 2.5 and 5.1 mm for carrots and 0.9-2.1 mm for Brazil nuts (Lucas and Luke, 1986). Other studies have reported differences in particle size distributions due to food type, yet indicate a lack of variability between and among individuals (Peyron et al, 2004). Intra-individual variability resulting in varied particle sizes may have implications for lipid bioaccessibility.…”
Section: Introductionmentioning
confidence: 93%
“…Other researchers have studied oral food processing (mastication, bolus formation, swallowing, etc), for example electromyography has been used to study the muscle activity while chewing peanuts (Hanawa, Tsuboi, Watanabe, & Sasaki, 2008;Kohyama & Mioche, 2004;Kohyama, Mioche, & Martin, 2002) and the resultant particle size distribution evaluated by various techniques such as wet sieving or laser diffraction (Peyron, Mishellany, & Woda, 2004). Flynn et al looked at particle size distribution of peanuts prior to swallowing and postulated multiple compartments within the mouth during mastication (Flynn et al, 2011).…”
Section: Texture Of Peanuts and Their Productsmentioning
confidence: 99%